O laptop educacional em sala de aula: práticas pedagógicas construídas - Neiva, Sonia Maria de Sousa Fabricio (2013)
This research aimed to investigate the teaching practices that occur with the use of educational laptop in the classroom, in order to implantation the Project One Computer per Student (UCA). The research took place at the State School Dom Alano Marie Du Noday Palmas (Tocantins, Brazil). The theoretical reference adopted treats the context of the knowledge society, education policies aimed to insertion of technology in schools, pedagogical practices through the use of technology and its articulation with the curriculum and project methodology, supported by Boaventura de Sousa Santos, Toffler, Dowbor , Hargreaves, Burbules, Mattelart, Fuks, Chauí, Almeida, Moraes, Pacheco, Apple, Silva, Gimeno Sacristán, Costa Monteiro and Loureiro, Batista, Cuban, Dewey, Schön, Goodson, Hernández, Prado, Freire, Papert, Almeida and Valente, Cappelletti, Esteban, among others. The theoretical-methodological principles are based on qualitative research supported in interpretive research of Erickson (1984, 1986, 1989). The data were collected from the following sources: documents related to UCA Project, Political- Pedagogical Project, field diary, interviews, focal group and questionnaires. The research subjects were students, parents, teachers, project managers and Training Brazil-UCA trainer at school. This study shows that the school lived with some different actions and conventional practices in the same time. The parents indicated that their children became more autonomous. Despite favorable to the insertion of the laptop at the school, parents had a wary eye about the changes that the computer causes in teaching practice, and they said that there was no change in the relationship between parents and the school. Managers betray the conception of the technologies being adornment, teaching and learning appendage. The students recognize that the class is more interesting. They can explore many tools. They learn better and in a different way. The teachers conceptions about the education laptop use in class is conditioned to technological appropriation, the technicalpedagogical support and influence of initial training. In the fifth and sixth years of the Dom Alano Marie Du Noday, the study revealed that two women teachers created loopholes. They gave new meaning to what they did when incorporated cooperative work, dialogue and reflection on teaching practice, establishing improvement in the teacher-student and student-student relationship. Those two women teachers had the student how the center teaching and learning process. Among other teachers of the Dom Alano Marie Du Noday, with whom there was also approach on the subject studied, it was verified that they walked toward a reflective practice, but the those teachers activities involving the laptop had not student how center of the process of teaching and learning. In many cases, the use of computer reinforces actions carried out with pencil and paper. Finally, it is considered that the answers are provisional and concerning the researched moment